Ergonomic risk assessment of field personnel of SICMA S.A.C. in civil construction works: Ergonomic risk assessment - Condori-Espinoza, Miryan Meldrid (2022)
Objective: To evaluate the ergonomic risk to field personnel of a civil construction company. Materials and methods: A descriptive, non-experimental, cross-sectional study was carried out on 33 workers. Data collection was carried out by applying a questionnaire for the identification of ergonomic risk referred to occupational factors, and it was evaluated using the REBA and OWAS methods in the ERGONAUTAS software. Results: From the application of the questionnaire, 66% of workers showed that they were exposed to medium risk. On the other hand, the REBA method reveals that the trunk and arms obtained scores of 3, considered high, and the formwork task predominated higher ergonomic risk. Likewise, the OWAS method indicates that, back and legs present higher scores, and sidewalk finishing and formwork tasks are the ones where dysergonomic postures prevail. Conclusions: Both methods indicate that, workers are exposed to medium risk levels, compromising the upper and lower body region, suffering in the future musculoskeletal pain. It is recommended to establish an ergonomics program that promotes the prevention of the development of musculoskeletal problems.